Axial crush behaviour of the aluminium alloy in-situ foam filled tubes with very low wall thickness. (15th May 2018) - Duarte, Isabel; Krstulović-Opara, Lovre; Vesenjak, Matej
Abstract: This paper presents the results of an experimental work carried out to fabricate and characterise the in-situ foam filled tubes (FFTs) made of aluminium alloys prepared by powder metallurgy method, using aluminium alloy tubes with extremely thin walls (∼0.6 mm). The fabrication procedure demonstrates that thin-walled tubes with extremely thin walls can support temperatures near to its melting temperature (∼700 °C) required to form a closed-cell aluminium alloy foam, consequently in-situ filling the tube. The mechanical performance of fabricated structures was evaluated using uniaxial compressive tests and infrared thermography. Results demonstrate that the benefits of the manufacturing process and its product, the FFTs (composite structures). Additionally, they reveal that this is a cost-effective solution to prepare efficient energy absorbing lightweight structures, allowing to adjust the weight and levels of the energy absorption, simultaneously. The results demonstrate that the promising in-situ FFTs with thinner outer tubes axially deform in an efficient mixed mode, showing superior energy absorption capability compared to the empty thin-walled tubes.